2019
DOI: 10.31883/pjfns-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Enzymatic Hydrolysate and Peptide Fractions from Perilla Seed Meal Protein

Abstract: Córdova-Murueta & García-Carreño, 2002]. Hydrolysates containing low molecular weight peptides are easier to digest and absorb than long polymeric proteins and are widely available in various foods and processed products [Megias et al., 2009]. Peptides produced via enzymatic hydrolysis of food proteins exhibit physicochemical properties that are different from those of the original proteins because of lower molecular weights and exposure of hydrophobic residues caused by changes in the molecular structure, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
2
8
0
1
Order By: Relevance
“…PSM is usually discarded or used in animal feeds as a low-value material. However, some studies [ 68 , 69 ] discovered that it still contained easily digestible proteins, polysaccharides, and substantial amounts of phenolic antioxidants, including RA. Our laboratory revealed that PSME clearly showed in vitro antimutagenicity, and antioxidant and anti-inflammatory activities [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSM is usually discarded or used in animal feeds as a low-value material. However, some studies [ 68 , 69 ] discovered that it still contained easily digestible proteins, polysaccharides, and substantial amounts of phenolic antioxidants, including RA. Our laboratory revealed that PSME clearly showed in vitro antimutagenicity, and antioxidant and anti-inflammatory activities [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of PSM protein hydrolysate and membrane fractions. The PSM protein hydrolysate was prepared following the method of Park and Yoon (2019). The PSM protein isolates (5% w/v) were suspended in 25 ml of 0.1 M phosphate buffer (pH 7.0), and hydrolyzed with 10 U of Flavourzyme at 50°C for 4 hours.…”
Section: Materialmentioning
confidence: 99%
“…A schematic representation of all the steps is shown in Figure 5 . A large body of literature has produced hydrolysates of protein with good emulsifying properties, but the majority omitted the stage of peptide identification (step iii), narrowing down the analysis to only their molecular weights or hydrophobicities [ 83 , 90 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. Some of the most comprehensive studies involving the three steps mentioned before are discussed next.…”
Section: Methodologies For Screening and Designing Emulsifying Peptidesmentioning
confidence: 99%